Otomycosis risk after non-suppurative middle ear surgery - Fatih Gul; Ozgenur Kocak; Ali Ozturk; Mehmet Ali Babademez (Brazilian Journal of Otorhinolaryngology)
Objectives: The aim of this study was to investigate the risk factors that may cause postoperative otomycosis in patients undergoing Chronic Nonsuppurative Otitis Media (CNSOM) surgery. Methods: In this retrospective study, 409 out of 523 patients met the inclusion criteria. 44 patients diagnosed with otomycosis CNSOM were analyzed. Perioperative factors were analyzed to determine the potential risks of otomycosis. The primary factors identified as contributing to otomycosis were firmly adherent cerumen, tympano-meatal flap positioning, and Diabetes Mellitus (DM). The study analyzed the patients’ follow-up six months after the surgical procedure. Otomycosis occurring within 30-days of surgery was classified as “early otomycosis”, while those occurring later were classified as “late otomycosis”. Results: Graft success at 6-months showed no significant difference between otomycosis and non-otomycosis groups. We found that the presence of DM, tympano-meatal flap positioning, and firmly adhered cerumen removal were significantly associated with the development of otomycosis. The logistic regression model was significant and explained 9.2% of the variation. Overall, individuals with the presence of advancement flap, DM, and cerumen removal status were respectively 2.0, 2.8, and 2.1 times more likely to have otomycosis. DM was the only risk factor identified in all three patients who developed late otomycosis. Conclusion: This study found that compromised epithelial integrity in the external auditory canal, non-epithelial areas, and reduced blood circulation were independent risk factors for postoperative otomycosis. Level of evidence: 4.